Five-Level Common-Emitter Inverter Using Reverse-Blocking IGBTs - Suroso Suroso; Toshihiko Noguchi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
In a high switching frequency operation of current-source inverter (CSI), a conventional way to obtain unidirectional power switches is by connecting discrete diodes in series with the high speed power switches, i.e. power MOSFETs or IGBTs. However, these discrete diodes will cause extra losses to the power converter. This paper presents experimental test results of high switching frequency five-level common-emitter CSI using the emerging unidirectional power switches, i.e. reverse blocking (RB)-IGBTs. Experimental tests were also conducted to compare the performance between power MOSFETs in series with the discrete diodes, and the RB-IGBTs having inherent reverse blocking capability. The results show that using RB-IGBTs, the efficiency of the power converter increase. However, it is also confirmed that the recently available RB-IGBTs have slow reverse recovery current than the discrete fast-recovery diodes connected in series with power MOSFETs.